Complete genome sequences of two Escherichia coli clinical isolates from Egypt carrying mcr-1 on IncP and IncX4 plasmids - Soliman, Ahmed M.; Ramadan, Hazem; Yu, Liansheng; Hisatsune, Junzo; Sugai, Motoyuki; Elnahriry, Shimaa S.; Nariya, Hirofumi; El-Domany, Ramadan A.; Shimamoto, Toshi; Jackson, Charlene R.; Shimamoto, Tadashi (Frontiers in Microbiology, 2022)
Colistin is a last-resort antibiotic used in the treatment of multidrug resistant Gram-negative bacteria. However, the activity and efficacy of colistin has been compromised by the worldwide spread of the mobile colistin resistance genes (mcr-1 to mcr-10). In this study, two clinical Escherichia coli strains, named EcCAI51, and EcCAI73, harbored mcr-1, showed multidrug-resistant phenotypes (with colistin MIC = 4 μg/ml), and belonged to phylogroup D: multilocus sequence type 1011 (ST1011) and phylogroup A: ST744, respectively. Findings revealed the existence of mcr-1 gene on two conjugable plasmids, pAMS-51-MCR1 (∼122 kb IncP) and pAMS-73-MCR1 (∼33 kb IncX4), in EcCAI51, and EcCAI73, respectively. The mcr-1-pap2 element was detected in the two plasmids. Additionally, the composite transposon (ISApl1-IS5D-pap2-mcr-1-ISApl1) was identified only in pAMS-51-MCR1 suggesting the potential for horizontal gene transfer. The two strains carried from 16 to 18 different multiple acquired antimicrobial resistance genes (ARGs). Additionally, two different multireplicon virulence plasmids (∼117 kb pAMS-51-Vr and ∼226 kb pAMS-73-Vr) carrying the sit operon, the Salmochelin siderophore iroBCDE operon and other several virulence genes were identified from the two strains. Hierarchical clustering of core genome MLST (HierCC) revealed clustering of EcCAI73, and EcCAI51 with global E. coli lineages at HC levels of 50 (HC50) to 100 (HC100) core genome allelic differences. To the best of our knowledge, this study presented the first complete genomic sequences of mcr-1-carrying IncP and IncX4 plasmids from human clinical E. coli isolates in Egypt. In addition, the study illustrated the mcr-1 broad dissemination in diverse plasmids and dissimilar E. coli clones.